Analysis of Road Damage Using the PCI Method: (Case Study on Tambak Osowilangon Road) - Arell Adritama; Diah Ayu Restuti (NAROTAMA UNIVERSITY, Indonesia, 2022)
Road is a land transportation infrastructure which includes all parts of the road, including complementary buildings and equipment intended for traffic that is at ground level, above ground or water level, above water level, except for trains, lorries and cable roads. The use of roads can help improve the economy, therefore periodic maintenance is needed. This research was conducted on the Tambak Osowilangon road using the location survey method and calculating the amount of damage and the PCI method. The results of this study are expected to be useful to determine the feasibility of the Tambak Osowilangon road as a benchmark for future improvements.